The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1536/ihj.51.68
|View full text |Cite
|
Sign up to set email alerts
|

Possible Contribution of Ischemia of the Conus Branch to Induction or Augmentation of Brugada Type Electrocardiographic Changes in Patients With Coronary Artery Disease

Abstract: SummaryRecent evidence suggests an association between vasospastic angina and Brugada syndrome. Here we present two cases of coronary artery disease who presented with ECG abnormalities which might have been provoked or enhanced by ischemia of the conus branch of the right coronary artery. The 12-lead ECGs demonstrated normal sinus rhythm in these two cases. Interestingly, a saddle back or coved type ST segment elevation in leads V1-V3 was documented either in the percutaneous transluminal angioplasty procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…This lesion was distal to the origin of the conus branch and therefore not affecting flow through it. In experiments involving acetylcholine and ergonovine to induce coronary spasm; the Brugada phenotype (BrP) could be induced especially when spasm was provoked in the right coronary arteries [2,3]. Increase in outward currents (I to ) and/or decrease in inward currents (I Ca ) induced by ischemia were postulated to result in augmentation of ST-segment elevation in the right precordial leads.…”
Section: Case Reportmentioning
confidence: 99%
“…This lesion was distal to the origin of the conus branch and therefore not affecting flow through it. In experiments involving acetylcholine and ergonovine to induce coronary spasm; the Brugada phenotype (BrP) could be induced especially when spasm was provoked in the right coronary arteries [2,3]. Increase in outward currents (I to ) and/or decrease in inward currents (I Ca ) induced by ischemia were postulated to result in augmentation of ST-segment elevation in the right precordial leads.…”
Section: Case Reportmentioning
confidence: 99%
“…In our case, in addition to the main culprit lesion at segment 7 in the LAD, a 75% stenotic lesion in the LMT might also have played a critical role in the genesis of the ECG changes, since the specific features as described by Hirano et al almost matched our case. On the other hand, recent reports have provided evidence that ischemia of the conus branch may induce Brugada-type ECG changes in patients with coronary artery disease (19)(20)(21)(22). In our case, the Brugada-like ECG pattern may have been caused by a LMT lesion leading to possible conus branch ischemia.…”
Section: Discussionmentioning
confidence: 45%
“…3,5 Matthews 5 reported that conus branch was occluded by injection to RCA during angiography. Eichhofer et al 4 reported that stent implantation in the right proximal coronary artery resulted in conus branch occlusion.…”
Section: Case Reportmentioning
confidence: 99%
“…There are 2 reports of Brugada-like ECG changes due to conus branch vasospasms with acetylcholine, which resulted in ventricular fibrillation or ventricular tachycardia. 3,6 Because Brugada syndrome can lead to ventricular fibrillation, and thus sudden death, treatment of conus branch occlusion is of clinical importance. In our case, penetration of a guidewire was attempted, and blood flow was restored without development of ventricular fibrillation or tachycardia.…”
Section: Case Reportmentioning
confidence: 99%